2017
DOI: 10.4028/www.scientific.net/msf.894.62
|View full text |Cite
|
Sign up to set email alerts
|

Performance Properties of Irradiated Recycled Polypropylene as a Compatibilizer in Recycled Polypropylene/Microcrystalline Cellulose Composites

Abstract: Effects of irradiated rPP compatibilizer, on the mechanical and thermal properties of recycled polypropylene/microcrystalline cellulose composites (rPP/MCC), are investigated. rPP is irradiated with an electron beam at dosages ranging from 10, 20, 30 to 50kGy. A matrix, containing of unirradiated and irradiated rPP (50:50 by ratio), is then added to 5, 20 and 40wt% MCC fibres. The composites are prepared using a twin screw extruder, followed by injection moulding. The properties are then characterized using te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 7 publications
(7 reference statements)
1
6
0
Order By: Relevance
“…Upon further analysis, it was observed that there had been a greater increase of the E' of the rPP:i-rPP/MCC composites as compared to the neat rPP. This implies that the addition of MCC fibers had enhanced the stiffness by restricting the flow of rPP matrix, which is in line with the results obtained from Young's modulus [3][4]. The storage moduli at specific temperatures; -50 °C (glassy region), +27 °C (room temperature) and +100 °C (possible use temperature) were selected as a means of comparing the effect of rPP:i-rPP ratio and irradiation dose.…”
Section: Gel Content Analysissupporting
confidence: 75%
See 4 more Smart Citations
“…Upon further analysis, it was observed that there had been a greater increase of the E' of the rPP:i-rPP/MCC composites as compared to the neat rPP. This implies that the addition of MCC fibers had enhanced the stiffness by restricting the flow of rPP matrix, which is in line with the results obtained from Young's modulus [3][4]. The storage moduli at specific temperatures; -50 °C (glassy region), +27 °C (room temperature) and +100 °C (possible use temperature) were selected as a means of comparing the effect of rPP:i-rPP ratio and irradiation dose.…”
Section: Gel Content Analysissupporting
confidence: 75%
“…Therefore, the present work aims to further investigate the effects of irradiated recycled PP on dynamic mechanical analysis (DMA) and water absorption properties from the developed composites. The results derived from this analysis is a supplementary research on an earlier study conducted by Lazim et al [2][3] and Samat et al [4].…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations